Sustainable Tourism Development in Tidore Islands City: Integrating Government, Community, and Marketing Strategies - Husaen Hasan; Budiyanto Budiyanto; Khuzaini Khuzaini (Cita Konsultindo Research Center, 2024)
This study aims to investigate the role of government, community, and marketing strategies in the development of tourism in Tidore Islands City, Indonesia. The study focuses on the importance of sustainable tourism development and the factors that contribute to it. 398 respondents were collected using accidental sampling. This research uses Structural Equation Modeling (SEM). The regression analysis revealed significant findings regarding the impact of various factors on tourism development and tourist visiting decisions. Both the marketing mix and local government policies exhibited significant effects on tourism development. Community involvement did not show a significant impact on tourism development. Regarding tourist visiting decisions, only government policies were found to have a significant effect. Community involvement did not significantly influence tourist visiting decisions, while tourism development itself did not significantly affect these decisions either. Tourism development mediated the influence of the marketing mix, government policies, and community involvement on tourist visiting decisions.